Media Communication Potential of Guidebooks in Black Sea Province - O. A. Boltuts (Научный диалог)
The article is devoted to the little-studied problem of the media communication potential of guidebooks in the Black Sea province in the context of the historical and cultural development of the region. The study of the existing gap is of undoubted interest for creating a complete picture of the nformation development of the Black Sea province in the process of cardinal economic and socio-cultural changes. The colonization of the Black Sea coast of the Caucasus is the most important component of the socio-economic and cultural policy of Russia. However, the process of settlement and land development, which began in the second half of the 19th century, was extremely slow and ineffective. The solution of the issue was impossible without a systematic information campaign on the part of the state. At the turn of the 19th—20th centuries, guidebooks for the Black Sea province became one of the important channels for disseminating information about the potential opportunities of the province in the field of agriculture, resort business, and tourism development. The author comes to the conclusion that the content of these guides paradoxically combined information of a historical and literary local history nature, contributing to the popularization of the cultural and natural originality of the Black Sea province. At the same time, like periodicals, he talked about existing problems and ways to solve them for further successful development of the region.